Note on a -Contour Integral Formula of Gasper-Rahman - Jian-Ping Fang (Abstract and Applied Analysis)
We use the -Chu-Vandermonde formula and transformation technique to derive a more general -integral equation given by Gasper and Rahman, which involves the Cauchy polynomial. In addition, some applications of the general formula are presented in this paper.